Case studies on the Quaternary andgeomorphology of Argentina: preface (Latin American Journal of Sedimentology and Basin Analysis, 2021)
During the last decades there was a worldwide renew interest in the study of the Quaternary and the Geomorphology, associated to the growing concern regarding the environment, the landscape use and the uncertainty about the climate change. Argentina was not an exception and many regions of all the provinces were the subject of geologic research to establish the Quaternary evolution of the landscape, and, in many cases, the significance of the inferred paleoclimatic changes. Meanwhile, some members of the geologic community of Argentina started to congregate and as a result the 1st Argentinian Congress of Quaternary and Geomorphology (CACyG for its Spanish acronym) was held in Santa Rosa (La Pampa), in the year 1999. Since then, five of those meetings were organized and the following one will find us next year, 8-12 April of 2015, in Ushuaia. Some of the contributions presented during the 5th CACyG (held in Río Cuarto during 2012) dealing with Quaternary and Geomorphology topics were selected to send an extended version to the Latin American Journal of Sedimentology and Basin Analysis to be published as an Special Issue. As a result of that initiative we are here presenting this Special Issue “Case studies on the Quaternary and Geomorphology of Argentina” with four original papers that received the standard peer-review of the LAJSBA and embrace different areas of central to north Argentina, from the Andean piedmont to the Pampean plain, the Pampean Ranges and up to the tropical Mesopotamia.